2012
DOI: 10.1002/clc.22058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Prognostic Value of Positron‐Emission Tomography Myocardial Perfusion Imaging Using Automated Software to Calculate Perfusion Defect Size

Abstract: Background: Myocardial perfusion imaging by positron-emission tomography (PET MPI) is regarded as a valid technique for the diagnosis of coronary artery disease (CAD), but the incremental prognostic value of PET MPI among individuals with known or suspected CAD is not firmly established. Hypothesis: Myocardial perfusion defect sizes as measured by PET MPI using automated software will provide incremental prognostic value for cardiac and all-cause mortality. Methods: This study included 3739 individuals who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Data from some of the patients (n=3,884) were included in prior publications. (2,4,6,8,9) Each center had institutional review board approval for the study. Study methods are shown in much greater detail in the Appendix section.…”
Section: Methodsmentioning
confidence: 99%
“…Data from some of the patients (n=3,884) were included in prior publications. (2,4,6,8,9) Each center had institutional review board approval for the study. Study methods are shown in much greater detail in the Appendix section.…”
Section: Methodsmentioning
confidence: 99%
“…The current study is comprised of 2383 patients who underwent clinically-indicated, rest-stress Rubidium-82 (Rb82) PET MPI for the evaluation of stable symptoms suggestive of obstructive CAD [20]. Patients with a known history of myocardial infarction, percutaneous coronary intervention, or coronary bypass surgery were excluded from the current study, as were those undergoing PET MPI for the evaluation of a possible acute coronary syndrome.…”
Section: Study Patientsmentioning
confidence: 99%
“…The software allows estimating the size of relative perfusion defects at multiple severity thresholds. In the current study, the PET parameter of interest is perfusion defect size defined as the percent of the LV myocardium with relative tracer uptake (perfusion) less than 60% of maximum [20,24]. Perfusion defect size was calculated at rest and during stress.…”
Section: Pet Mpi Perfusion Measurementsmentioning
confidence: 99%
See 2 more Smart Citations